(untitled) (Journal of Atomic and Molecular Sciences, 2015)
By using multi-reference configuration interaction method and large all-electron basis sets aug-cc-pwCV5Z, we have calculated the dense potential energy curves (PECs) of 1¹Σ^+, 1³Σ^+, 1¹Π, and 1³Π states of LiBe^+ molecule. Based on the obtained PECs, the analytical potential energy functions (APEF) have been constructed with a Morse long-range potential function and nonlinear least squares method. The rotational and vibrational energy levels of the four states are determined by solving Schrödinger equation of nuclear movement with the APEFs. The spectroscopic parameters are deduced with the obtained rotational and vibrational energy levels.